Amine modified tannin gel for adsorptive removal of Brilliant Green dye. Issue 1 (March 2016) - Akter, Nahida; Hossain, Md. Asjad; Hassan, M. Jobaer; Amin, M.K.; Elias, M.; Rahman, Mohammed M.; Asiri, Abdullah M.; Siddiquey, Iqbal A.; Hasnat, Mohammad A.
Graphical abstract: Brilliant Green is adsorbed on TG and ATG through multi-linearity process, which indicate that two or more steps were involved during the process. TG prefers intra-particles diffusion mechanism, meanwhile ATG favours external surface adsorption mechanism. Abstract: The potentiality of tannin gel (TG) and amine modified tannin gel (ATG) has been found as highly effective, eco-friendly and cheap adsorbents for removal of Brilliant Green (BG) dye. In each case, the most efficient adsorption occured at pH 7 with 88.38% for TG and 94.05% removal for ATG, respectively. The adsorption kinetics for TG was found to follow pseudo-first-order kinetic model along with intraparticle diffusion, and for ATG it was found to follow pseudo-second order kinetic model. The experimental data were found to best fit with langmuir isotherm ( r 2 > 0.99 for both gels) with maximum monolayer adsorption capacity of 8.55 mg/g for TG and 20.41 mg/g for ATG. The negative values of Gibb's free energy (Δ G °) of both gels indicate the spontaneous nature of the adsorption process.The positive values of Δ H ° with respect to both gels suggest the endothermic adsorption nature along with positive values of entropy changes (Δ S °).